2014
DOI: 10.1103/physrevd.90.103522
|View full text |Cite
|
Sign up to set email alerts
|

Tidal capture of primordial black holes by neutron stars

Abstract: The fraction of primordial black holes (PBHs) of masses 10 17 -10 26 g in the total amount of dark matter may be constrained by considering their capture by neutron stars (NSs), which leads to the rapid destruction of the latter. The constraints depend crucially on the capture rate which, in turn, is determined by the energy loss by a PBH passing through a NS. Two alternative approaches to estimate the energy loss have been used in the literature: the one based on the dynamical friction mechanism, and another … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 29 publications
3
41
0
Order By: Relevance
“…The specific power spectra of the curvature perturbations and the resultant PBH mass spectra are shown in Fig. 1 and 2 for two parameter sets (17) and (26). The inflection point corresponds with ∼ 10 22 g PBHs and they constitute the bulk of DM in our model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific power spectra of the curvature perturbations and the resultant PBH mass spectra are shown in Fig. 1 and 2 for two parameter sets (17) and (26). The inflection point corresponds with ∼ 10 22 g PBHs and they constitute the bulk of DM in our model.…”
Section: Discussionmentioning
confidence: 99%
“…However, observations of globular clusters show no evidence of significant dark matter content in such systems [13,14]. Furthermore, it was suggested that tidal deformation of a neutron star could lead to an efficient energy dissipation and capture of a black hole, leading to stronger constraints [15], but such energy losses are uncertain, and they are likely to be suppressed for realistic parameters and velocities in excess of the speed of sound [16,17], so that no new constraints can be derived, and the window for PBH dark matter remains open.…”
Section: Introductionmentioning
confidence: 99%
“…Note that a certain fraction of the dark matter is in the form of particles with mass m much smaller than that of PBHs. The value of f is constrained for a wide range of M bh and can be as large as 0.1 for M bh < ∼ 0.1M⊙ while much severer constraints, f < ∼ 10 −8 , are obtained for M bh > ∼ 10 3 M⊙ (Tisserand et al 2007;Ricotti et al 2008;Capela et al 2013a;Capela et al 2013b;Defillon et al 2014;Pani & Loeb 2013;Pani & Loeb 2014;Griest et al 2014). Henceforth, we assume that f ≪ 1.…”
Section: Binary Pbhsmentioning
confidence: 99%
“…Attempts have been made to place bounds between ∼ 10 17 gm -10 24 gm [11,13,14], but are subject to uncertainties [11,15].…”
Section: Triggering Runaway Fusionmentioning
confidence: 99%